The Influence of Analytical Intelligence on the Internal Auditor's Skill to Evaluate Risks.: Evidence from Iraq - Sahib, Abdulrasool Abdulabbas; Wahhab, Asaad Mohammed Ali (Technium Social Sciences Journal, 2023)
The study aims to improve the reality of internal auditing in Iraq by employing analytical intelligence after determining its impact and its relationship to the internal auditor's ability to assess risks and to include this evaluation in the auditor's report, which must be of a high level of skill to achieve the highest level of professionalism and stay abreast of developments in the profession. Review through the application of international auditing standards, and to achieve the objectives of the study, a questionnaire was used, 240 of which were distributed to a sample of internal auditors, and 220 of which were returned for analysis to measure the correlation and influence relationship between the variables of the study, and it was determined that successful intelligence has an apparent effect and relationship. Positive in enhancing the ability of internal auditors to assess risks, as the value of the correlation between the first independent dimension (analytical intelligence) and the power of the internal auditor to assess risks reached 0.275, which is a positive value with significant significance at the 5% level, and that analytical intelligence influences positively and significantly at the 5% level in the internal auditor's ability to assess risks by 0.18 if the internal auditor has a high level of analytical intelligence.